Jejak Langkah Dakwah Al-Qur’an di Tanah Purnakarya, Kecamatan Tanralili, Kabupaten Maros: The Journey of Qur’anic Da’wah in the Land of Purnakarya, Tanralili, Maros - Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Community Service Program (KKN) is a compulsory course that must be undertaken by every student. The Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) conducts the KKN program once a year, and in 2025, STIBA Makassar is carrying out the KKN in Tanralili Sub-district, encompassing 7 villages and 1 urban village, for a duration of 57 days, from February 26, 2025, to April 24, 2025. This program aims to develop Qur’anic da’wah in the Purnakarya region, Tanralili Sub-district, Maros Regency. This area has strong Islamic potential but has yet to be fully cultivated through systematic and sustainable religious development efforts. Using a participatory approach, the program involves community leaders, Qur'an teachers, and youth in building a community-based Qur’anic literacy culture. The methods used include field observation and Qur’anic learning based on tajwid and memorization (tahfiz). The outcomes of the program show increased enthusiasm among residents in attending Qur’an classes. This KKN highlights the importance of sustained, locally rooted da’wah and the urgent need to revitalize Qur’anic values in the social life of the community. The main programs carried out include TK-TPA teaching, dirosah and tahsin classes, Tahfidz Camp, and religious holiday (THR) activities.